Study guides

Q: Factor X2 plus 6X plus 4?

Write your answer...

Submit

Related questions

x2 + 6x + 8 = (x + 4)(x + 2)

x2 + 6x + 8 =(x + 2)(x +4)

(x - 4)(x - 2)

x - 4 APEX

X - 4

x3 + x2 - 6x + 4 = (x - 1)(x2 + 2x - 4)

4

4(x2 - 6x + 13)

x3 + 3x2 - 6x - 8 = (x - 2)(x2 + 5x + 4) = (x - 2)(x + 1)(x + 4)

(x - 2)(x - 4)

(X + 2)(X + 4) Factored

The quadratic expression x2+6x+8 when factorised equals (x+2)(x+4)

(x - 2)(x - 4) are the factors, assuming "= 0" was omitted.

If that's 6x - 40, and one of the choices is either (x + 10) or (x - 4), pick that one.

You didn't bother to list the binomials to choose from, but the two binomial factors of x2 + 6x - 40 are (x + 10) and (x - 4)

x3 + 4x2 + 6x + 24 = (x2 + 6)(x + 4)

(x + 4)(x + 2)

x2 + 6x + 8 = 0 Solve for x.X = -2 or X = -4

x3 + x2 + 4x + 4 = (x2 + 4)(x + 1)

(x - 2)(x - 4)

6x+4 factor: 2(3x+2)

6x(3x2 - x + 4)

Dividing all terms by 4 gives: x2-6x+8 = (x-2)(x-4) when factored

x2+6x-40 = 0 (x+10)(x-4) = 0 x = 4 or x = -10

x²+6x+9=49 x²+6x-40=0 x1=-6/2 - Square root of ((6/2)²+40) x1=-3 - 7 x1= -10 x2=-6/2 + Square root of ((6/2)²+40) x2=-3 + 7 x2= 4